Ikhtiar Pendidikan Karakter pada Perguruan Tinggi - Wutsqah, Urwatul (Al-aqidah | Jurnal Studi Islam, 2018)
Education has a great responsibility towards the development of a civilized and civilized young generation. The incessant globalized ?digital? culture with sparkling lifestyle accessories has ?teased? young people into hedonistic and materialist cultures. Character education is needed to form a noble person, so that his life is not arid of values, religion and far from the culture of the nation. Students as a guide to change, play a strategic role and function. The main role of students, as: agents of change, social control and moral strength. Student characters can not be formed automatically, but developed through educational institutions, non-formal, formal and informal. Character education has become a national movement, from early childhood education (PAUD) to college.